2021
DOI: 10.1111/wre.12468
|View full text |Cite
|
Sign up to set email alerts
|

Phytodiversity in Christmas‐tree plantations under different management regimes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, they provide open to semi‐open and heterogeneous habitat structures, which are known to be beneficial for the majority of farmland specialists (Fartmann et al, 2018; Newton, 2017; Ram et al 2020). Accordingly, recent studies found that Christmas tree plantations can harbour rich biodiversity, regardless of the rather intensive farming practice (e.g., Bagge et al, 2012; Fartmann et al, 2018; Gailly et al, 2017; Hagge et al, 2019; Streitberger & Fartmann, 2020, 2021). This especially applies to farmland birds (e.g., Fartmann et al, 2018; Gailly et al, 2020; Gailly et al, 2017), which rank among the most severely threatened species throughout Europe (BirdLife International, 2017; Reif et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, they provide open to semi‐open and heterogeneous habitat structures, which are known to be beneficial for the majority of farmland specialists (Fartmann et al, 2018; Newton, 2017; Ram et al 2020). Accordingly, recent studies found that Christmas tree plantations can harbour rich biodiversity, regardless of the rather intensive farming practice (e.g., Bagge et al, 2012; Fartmann et al, 2018; Gailly et al, 2017; Hagge et al, 2019; Streitberger & Fartmann, 2020, 2021). This especially applies to farmland birds (e.g., Fartmann et al, 2018; Gailly et al, 2020; Gailly et al, 2017), which rank among the most severely threatened species throughout Europe (BirdLife International, 2017; Reif et al, 2008).…”
Section: Introductionmentioning
confidence: 99%